Comparing employability priorities of emerging and experienced interior designers. Issue 1 (1st December 2019) - Huber, Amy M.; Waxman, Lisa K.
While design scholars have long explored the design process and its underlining decision-making tactics, few empirical studies have examined other judgements that may also influence design practice, such as the skills and contributions of new hires and their fit with their firms' management style, culture and values. To probe employability priorities, this study first explored broad-based and discipline-specific literature, accreditation standards, and recent position announcements from interior design practice. Next, in order to define those skills and traits most highly valued in commercial interior design, new quantitative survey data was collected from emerging interior designers, and, in turn, was compared to extant research findings on the hiring priorities of experienced management practitioners within the interior design consultancy industry. Survey responses support earlier findings emphasizing soft skills while contributing to the literature by highlighting differing priorities between experienced interior designers and those whom they are likely to hire (i.e. emerging design professionals). Such differing priorities may have resonance in allied design disciplines, which is discussed with implications for design management hiring practice, emerging design professionals' employability efforts, and practices of educators aiming to enhance the employability of design graduates.